Efektivitas Metode Drill Play untuk Meningkatkan Kemampuan Bahasa Ekspresif pada Anak Intellectual Disability - Khalida, Rahmi; Firdaus, Firdaus (Journal of Special Education Lectura, 2025)
Children with intellectual disabilities often experience delays in language development, particularly in expressive language skills, which play an important role in everyday communication. The Drill Play method, implemented in speech therapy programs for children that combine repetitive exercises with a play-based approach, is designed to increase motivation and the effectiveness of language learning in children with special needs. This study aims to analyze the effectiveness of the Drill Play method in improving expressive language skills in children with intellectual disabilities. The research method uses an experimental design with a one-group pretest-posttest approach. The study sample consists of children with intellectual disabilities and expressive language disorders. The intervention was conducted over several sessions of a specific duration, using repetitive exercises.